Biology-Orientated Synthesis of Putrescine Bisamides Gigantamide A, Dasyclamide, and Cucullamide - Batwal, Ramesh U.; Argade, Narshinha P. (Synthesis, 2013)
Starting from putrescine and the requisite carboxylic acids, first syntheses of bioactive natural products gigantamide A, dasyclamide, and cucullamide were accomplished in very good overall yields using an appropriate sequence of dehydrative coupling reactions. The syntheses of the corresponding dehomo analogues of these natural products are also described. Regioselective diisobutylaluminum hydride reduction of an unhindered carbonyl group in citraconimide is the key step.
Keywords: diamines; dehydrative coupling reactions; regioselective reduction; natural and unnatural bisamides; synthesis